The role amenities play in spatial sorting of migrants and their impact on welfare: Evidence from China - Zhang, Yunda (PLOS ONE, 2023)
From 2005 to 2015, China’s high-skilled labor was increasingly concentrated in cities with high wages and high rents, while a narrowing of the wage gap between high- and low-skilled labor showed an opposite trend to an increase in geographic sorting. In this research, I estimated a spatial equilibrium structural model to identify the causes of this phenomenon and its impact on welfare. Changes in local labor demand essentially led to an increase in skill sorting, and changes in urban amenities further contributed to this trend. An agglomeration of high-skilled labor raised local productivity, increased wages for all workers, reduced the real wage gap, and widened the welfare gap between workers with different skills. In contrast to the welfare effects of changes in the wage gap driven by exogenous productivity changes, changes in urban wages, rents, and amenities increased welfare inequality between high- and low-skilled workers, but this is mainly because the utility of low-skilled workers from urban amenities is constrained by migration costs; if migration costs caused by China’s household registration policy were eliminated, changes in urban wages, rents, and amenities would reduce welfare inequality between high- and low-skilled workers to a greater extent than a reduction in the real wage gap between these two groups.